1998
DOI: 10.1007/s001070050329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of sawn timber from Norway spruce

Abstract: Dynamic and static tests were performed on 523 lumber specimens of Norway spruce (Picea abies) of three different cross sectional sizes: 38 x 89 mm 2, 38 x 140 mm 2, and 38 x 184 mm 2. Specific material characteristics for the lumber are presented. The tests also enabled comparison between results from two testing methodologies. The mean value for the modulus of elasticity established from the dynamic tests was found to be approximately 10% higher than the corresponding value established from static tests. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 2 publications
4
21
1
Order By: Relevance
“…The coefficient of determination (R 2 ) shows the degree of description given by the dependence or degree of reliability of MOE calculated according to the given equation. Dynamic MOE generally shows a lower correlation of dependence with bending strength than applies to the dependence of dynamic MOE and static MOE (Bodig and Jayne 1982;Larsson et al 1998;Guntekin et al 2013;Baar et al 2015). For samples with a lower defect content (especially knots), these dependencies increase and the prediction of mechanical properties by dynamic testing is more accurate (Ayarkwa et al 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of determination (R 2 ) shows the degree of description given by the dependence or degree of reliability of MOE calculated according to the given equation. Dynamic MOE generally shows a lower correlation of dependence with bending strength than applies to the dependence of dynamic MOE and static MOE (Bodig and Jayne 1982;Larsson et al 1998;Guntekin et al 2013;Baar et al 2015). For samples with a lower defect content (especially knots), these dependencies increase and the prediction of mechanical properties by dynamic testing is more accurate (Ayarkwa et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of CL, on the contrary, a significant statistical deviation was registered between static MOE and both dynamic methods (15.5% for MTG and 12.7% for accelerometer). The difference between the results of the dynamic and static tests of solid wood may be caused by the viscoelastic properties of wood, which play a role in the static bending test; additionally, the duration of the load on the tested element, which causes creeping and distorts real MOE, is important (Bodig and Jayne 1982;Larsson et al 1998). If the creeping effect were eliminated, the deviations between the static and dynamic values would decrease (Teranishi et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…It should further be noted that the static MOE represents a local stiffness over the grade determining defect while the dynamic MOE represents a mean value over the full specimen. A study carried out by Larsson et al (1998) on more than 500 timber specimens of Norway spruce comprises results on dynamic axial stiffness, dynamic bending stiffness, static bending stiffness and bending strength. However, the results in terms of coefficients of determination do not indicate that the dynamic bending stiffness correlates stronger to the bending strength than the dynamic axial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Steffen et al (1997) reported that density and modulus of elasticity varied considerably over the cross-section of Norway spruce boards. Larsson et al (1998) found a coefficient of determination of 0 . 26 between bending strength and density.…”
Section: Materials Characterisation Studies Involving Timbermentioning
confidence: 97%